2018
DOI: 10.1590/s1677-5538.ibju.2017.0318
|View full text |Cite
|
Sign up to set email alerts
|

Impact on sexual function of surgical treatment in rectal cancer

Abstract: IntroductionThe development of new surgical techniques and medical devices, like therapeutical multimodal approaches has allowed for better outcomes on patients with rectal cancer (RCa). Owing to that, an increased awareness and investment towards better outcomes regarding patients’ sexual and urinary function has been recently observed.AimEvaluate and characterize the sexual dysfunction of patients submitted to surgical treatment for RCa.Materials and MethodsAn observational retrospective study including all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 16 publications
1
17
0
2
Order By: Relevance
“…The type of surgical procedure was also related to worse outcomes ( P = 0.005) with most patients treated with APR reporting sexual dysfunction. Moreover, an observational retrospective study performed by Costa et al[49] in 2018 found the presence of a stoma post-operatively to be associated with sexual dysfunction. Attaallah et al[50] compared rates of sexual dysfunction in patients treated with laparoscopic TME and those treated with open TME in 187 patients and reported reduced rates of dysfunction in the laparoscopic arm compared to open.…”
Section: Complications Of Radiotherapymentioning
confidence: 99%
“…The type of surgical procedure was also related to worse outcomes ( P = 0.005) with most patients treated with APR reporting sexual dysfunction. Moreover, an observational retrospective study performed by Costa et al[49] in 2018 found the presence of a stoma post-operatively to be associated with sexual dysfunction. Attaallah et al[50] compared rates of sexual dysfunction in patients treated with laparoscopic TME and those treated with open TME in 187 patients and reported reduced rates of dysfunction in the laparoscopic arm compared to open.…”
Section: Complications Of Radiotherapymentioning
confidence: 99%
“…Data on the characteristics of respondents in this study were diabetes mellitus 13.5%, respondents with hypertension 18.9%, the majority of respondents had a history of consuming drugs, namely 54%, where the most consumed drugs were MST 18 drugs, 9%, the majority of respondents with cancer namely 91.9% and the majority of respondents undergoing chemotherapy 91.9%. According to Costa et al diabetes, hypertension, and the use of sedatives are risk factors for sexual dysfunction (17) . The results of the bivariate analysis showed a significant relationship between biological factors and the incidence of sexual dysfunction in patients with a stoma (p = 0.00).…”
Section: Discussionmentioning
confidence: 99%
“…[59] SONUÇ Sonuç olarak kanser, gerek hastalığın kendisi gerekse uygulanan tedaviler nedeniyle, birtakım fizyolojik değişimlere yol açmasının yanı sıra, bireylerin ve aile üyelerinin yaşam kalitesinin azalmasıyla ilişkili olarak depresyon, kaygı, benlik saygısının bozulması, stres, psikolojik ve duygusal refahta azalma gibi ciddi ve şiddetli psikososyal etkilere neden olmaktadır. [63][64][65][66][67][68] Bireyin fiziksel sağlık, psikolojik durum, bağımsızlık seviyesi, kişisel inançları, sosyal ilişkileri gibi varlığının tüm yönlerini kapsayan yaşam kalitesinin önemli bir boyutu olan cinsellik de bu süreçte çok boyutlu olarak etkilenmektedir. [66,69,70] Hakem Değerlendirmesi…”
Section: öZunclassified